Availability of Facilities to Encourage Clean and Healthy Living Behavior - Pertiwi, Wiwik Eko; Nasiatin, Titin (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The habit of CHLB in school-age children can be influenced by various factors, including knowledge, attitudes, parental education level and the availability of infrastructure that supports students' CHLB. This study aims to determine the factors associated with CHLB in elementary school students. The study was conducted in February-August 2019 in all northern elementary schools in Kramatwatu District with a sample of 170 grade 5 elementary school students who were taken by purposive sampling. This study used a cross-sectional design with bivariate analysis. This study shows that as many as 45.3% of respondents have a bad CHLB, the level of education is in the high category (SMA), have a good level of knowledge (80%), a positive attitude (51.8%), good infrastructure (70%) and there is a relationship between the availability of infrastructure and CHLB . The availability of infrastructure encourages changes in CHLB in elementary school students.